O espaço social dos “Negócios de Impacto” no Brasil: o caso Artemisia - Lourenço, Bruna Scanavachi (2018)
The aim of this work was to understand what is Social Business from the organization Artemisia and for this the organization specialized in impact businesses and the agents around it was the object of the paper. The new business model that permeates the spheres of the social world and the traditional business world in search of solutions to societal problems, the so-called Social Business or Impact Business, is a new type of organization that does not fit into the category of organizations which are solely and exclusively aimed at maximizing profits, just as it is not a non-profit organization. This work seeks to contribute to the understanding of what is a Social Business from a sociological perspective, starting from the premise that this new organizational model starts from the interaction of agents coming from diverse spaces, that influence and were influenced by the social structures of space in that emerged. Based on the idea that the social universes are constructed by deeper structures, often invisible at first sight, Bourdieu's notion of social space (1996) was the basis for the understanding that in transforming the business model, the proposal of the Social Business also alters, at least in theory, the market logic of the economic world where it is inserted. Understanding how the social space is formed, who are and how the agents are positioned in relation to the economic system is the starting point of the effort to understand the new organizational model. In addition to understanding the functioning of the Artemisia organization, an outline of the social space formed around it was made. Assuming that the social structure creates spaces of power and that the position of the agents in this structure is directly related to the distribution of the different types of capital (BOURDIEU, 1996), the agents of the space considered were identified and their economic and cultural capitals were analyzed. The constitution of the social space about Artemisia revealed that although the new organizational model integrates logics of distinct spaces, few agents from spaces with a predominance of social impact logic were found, besides the presence of heirs and other agents with capital acquired in the space of traditional businesses. The analysis of organizations that act as intermediaries in space revealed that they do not compete with each other, because although they could intuitively be considered as competitors since they present similar proposals and services to the same target public, they act as partners and have several agents in common in its structure. The analysis of the organizations that have connections with Artemisia also revealed that although not yet consolidated, it is possible to observe a strategy of articulation of investments of the public sector in progress.